2018
DOI: 10.3390/ijms19020481
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Aging on Cardio and Cerebrovascular Diseases

Abstract: A growing number of evidences report that aging represents the major risk factor for the development of cardio and cerebrovascular diseases. Understanding Aging from a genetic, biochemical and physiological point of view could be helpful to design a better medical approach and to elaborate the best therapeutic strategy to adopt, without neglecting all the risk factors associated with advanced age. Of course, the better way should always be understanding risk-to-benefit ratio, maintenance of independence and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 257 publications
(280 reference statements)
2
64
0
Order By: Relevance
“…Those changes were particularly apparent in males ( Supplementary Table S2). Previous studies have found that CO does not change, whereas SV increases with aging in humans [12,25].…”
Section: Discussionmentioning
confidence: 79%
“…Those changes were particularly apparent in males ( Supplementary Table S2). Previous studies have found that CO does not change, whereas SV increases with aging in humans [12,25].…”
Section: Discussionmentioning
confidence: 79%
“…In patients with high risk, physiological aging (CA= BA) was observed in 9.4% (9/96) cases, in 31.3% (30/96) cases, a slowed aging rate (SAR) was recorded, and an accelerated aging rate (AAR) was observed in 59.4% (57/96) patients. As evidenced by numerous studies various factors may contribute to accelerated aging [10]. Thus, Emelyanov V.V.…”
Section: Resultsmentioning
confidence: 99%
“…Although prolonged lifespan does not always correspond to health span, extreme longevity is often accompanied by reduced or delayed morbidity (111,112). This led to the hypothesis that the aging-related decay is neither necessary nor irreversible (111).…”
Section: Genetics Of Extreme Longevity: Can This Inform New Therapy Smentioning
confidence: 99%